India as an emerging market - Banerjee, Madhumita (Henry Stewart Talks, 2009)
Emerging markets, Country/market attractiveness and complexities, Market assessment: critical issues, Growth drivers for regions and cities, How are organizations identifying international business and marketing opportunities?, Market entry and development challenges and opportunities